Adrenocorticotropic Hormone Secreting Pheochromocytoma Underlying Glucocorticoid Induced Pheochromocytoma Crisis - Gil A. Geva; David J. Gross; Haggi Mazeh; Karine Atlan; Iddo Z. Ben-Dov; Matan Fischer (Case Reports in Endocrinology)
Context. Pheochromocytomas are hormone secreting tumors of the medulla of the adrenal glands found in 0.1–0.5% of patients with hypertension. The vast majority of pheochromocytomas secrete catecholamines, but they have been occasionally shown to also secrete interleukins, calcitonin, testosterone, and in rare cases adrenocorticotropic hormone. Pheochromocytoma crisis is a life threatening event in which high levels of catecholamines cause a systemic reaction leading to organ failure. Case Description. A 70-year-old man was admitted with acute myocardial ischemia following glucocorticoid administration as part of an endocrine workup for an adrenal mass. Cardiac catheterization disclosed patent coronary arteries and he was discharged. A year later he returned with similar angina-like chest pain. During hospitalization, he suffered additional events of chest pain, shortness of breath, and palpitations following administration of glucocorticoids as preparation for intravenous contrast administration. Throughout his admission, the patient demonstrated both signs of Cushing’s syndrome and high catecholamine levels. Following stabilization of vital parameters and serum electrolytes, the adrenal mass was resected surgically and was found to harbor an adrenocorticotropic hormone secreting pheochromocytoma. This is the first documented case of adrenocorticotropic hormone secreting pheochromocytoma complicated by glucocorticoid induced pheochromocytoma crisis. Conclusion. Care should be taken when administering high doses of glucocorticoids to patients with suspected pheochromocytoma, even in a patient with concomitant Cushing’s syndrome.